Dilemmas in developing models for long-term drought risk management: The case of the National Water Model of the Netherlands. (September 2021) - Mens, Marjolein; Minnema, Bennie; Overmars, Koen; van den Hurk, Bart
Abstract: Strategic decision-making on long-term drought risk management can be supported by integrated assessment models to explore uncertain future conditions and potential policy actions. Such models have to meet many – sometimes conflicting – requirements posed by policy-makers, model developers, and stakeholders. This paper discusses the case of the National Water Model (NWM) that is applied for national policy-making on drought risk management in the Netherlands. The case demonstrates that the chosen assembled model set-up (in which several existing models are combined) is cost-effective and increases stakeholder acceptance, but also leads to high model complexity and computation time. To be effective for policy-making, integrated assessment models need to produce relevant model outcomes that are accepted by stakeholders, within acceptable time and cost limits. For this, the model set-up must support simulations at different aggregation levels (allowing both detailed analysis and exploratory analysis of many scenario/strategy combinations) while maintaining internal consistency. Highlights: Decision-making for drought risk management requires Integrated Assessment Models. Integrated Assessment Models must meet many – sometimes conflicting – requirements. There is a clear trade-off between model complexity and timeliness. Effective models are those that allow simulations at different aggregation levels.